Lithium iron phosphate positive electrode material, preparation method thereof and lithium battery
Spherical iron phosphate particles were prepared by combining crystal form regulation method and seed method, and carbon-coated lithium iron phosphate was prepared in combination with rotary kiln vapor deposition technology, which solved the problem of insufficient performance of lithium iron phosphate batteries under fast charging, and achieved lithium batteries with high energy density and high rate performance.
Patent Information
- Application Number
- CN202411646336.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The electronic conductivity and Li+ diffusion rate of lithium iron phosphate batteries are low under fast charging, resulting in an increase in electrochemical polarization phenomenon and a higher internal resistance, which affects its rate performance, and irregular morphology affects the energy density.
Spherical iron phosphate particles were prepared by combining crystal form regulation and seed method, and spherical carbon coated lithium iron phosphate with small and large particle sizes were prepared by using rotary kiln vapor deposition and different sintering temperatures, and mixed according to mass ratio to form a grading to improve the compaction density of the material.
The compaction density and electrical performance of lithium iron phosphate positive electrode material are improved, the energy density and rate performance of lithium batteries are enhanced, and the fast charging needs are met.
Smart Images

Figure CN119612474A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion battery materials, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, and a lithium battery. Background Art
[0002] With the development of society, the theoretical range of new energy vehicles continues to increase, but the actual range has not yet reached the theoretical value. In addition, the charging time is long. These problems have brought many inconveniences in practical applications. In response to the above shortcomings, the current solution strategy is mainly focused on improving the energy density and fast charging performance of lithium batteries. Lithium iron phosphate batteries have occupied more than half of the power lithium battery market share due to their excellent safety performance, long cycle life and low cost.
[0003] Although lithium iron phosphate batteries have developed rapidly, they still face technical bottlenecks in fast charging performance. Due to the structural defects of lithium iron phosphate (LiFePO4), its electronic conductivity and Li + The diffusion rate is low. In the case of high-rate discharge, lithium ions cannot escape in time, which increases the electrochemical polarization of lithium iron phosphate and increases the internal resistance, affecting its rate performance and failing to meet the demand for fast charging. Secondly, due to the irregular morphology and different sizes of lithium iron phosphate, its compaction density is low, which in turn affects the energy density of lithium iron phosphate batteries.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a lithium iron phosphate positive electrode material and a preparation method thereof and a lithium battery, aiming to increase the compaction density of the lithium iron phosphate positive electrode material and thereby increase the energy density of the corresponding lithium battery.
[0006] The present invention is achieved in that: In a first aspect, the present invention provides a method for preparing a lithium iron phosphate positive electrode material, which comprises the following steps: S1, subjecting a first iron source solution and a first phosphorus source solution to a first coprecipitation reaction in the presence of a polymer monomer to obtain iron phosphate seed crystals; S2, subjecting the second iron source solution and the second phosphorus source solution to a second coprecipitation reaction in the presence of the polymer monomer and the iron phosphate seed crystals to obtain iron phosphate dihydrate; S3, mixing the ferric phosphate dihydrate, the lithium source and the carbon source and spray drying the mixture to obtain a spray material; S4, placing the spray material in a rotary kiln for sintering to obtain carbon-coated lithium iron phosphate; wherein different sintering temperatures are set to respectively prepare a first carbon-coated lithium iron phosphate and a second carbon-coated lithium iron phosphate; S5. Mix the first carbon-coated lithium iron phosphate and the second carbon-coated lithium iron phosphate according to a mass ratio to obtain a lithium iron phosphate positive electrode material.
[0007] In an optional embodiment, the concentration of the first iron source solution and the first phosphorus source solution is 1 mol / L to 2 mol / L, and the concentration of the second iron source solution and the second phosphorus source solution is 0.1 mol / L to 0.5 mol / L.
[0008] In an optional embodiment, the amount of the iron phosphate seed crystals added is 10% to 25% of the total mass of the second iron source and the second phosphorus source.
[0009] In an optional embodiment, the polymer monomer satisfies at least one of the following (1) to (2): (1): The polymer monomer includes at least one of pyrrole, aniline and thiophene; (2): In steps S1 and S2, the amount of the polymer monomer used per gram of iron source is 0.01 g to 0.2 g.
[0010] In an optional embodiment, the first coprecipitation reaction and / or the second coprecipitation reaction satisfies at least one of the following (3) to (6): (3): The coprecipitation reaction includes adding a morphology control agent, wherein the morphology control agent includes at least one of polyethylene glycol, polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide, and the mass of the morphology control agent is 0.01% to 5% of the mass of the first iron source or the second iron source; (4): The coprecipitation reaction includes adding an oxidant and / or a pH adjuster, wherein the oxidant includes hydrogen peroxide and the pH adjuster includes ammonia water; (5): The pH of the coprecipitation reaction is 1.5~3.0, and the temperature of the coprecipitation reaction is 75℃~95℃; (6): After the coprecipitation reaction is completed, it also includes aging and solid-liquid separation, and drying the separated solid product; wherein the aging time is 0.5h~6h, the drying temperature is 100℃~130℃, and the drying time is 2h~5h.
[0011] In an optional embodiment, the sintering in step S4 includes sintering for 3h~8h and then introducing a reducing gas to continue sintering for 1h~5h; The reducing gas includes at least one of acetylene and methane, and the gas flow rate is 0.01L / min~0.15L / min.
[0012] In an optional embodiment, the preparation method satisfies at least one of the following (7) to (9): (7): The sintering temperature of the first carbon-coated lithium iron phosphate is 730°C to 770°C; (8): The sintering temperature of the second carbon-coated lithium iron phosphate is 800°C to 830°C; (9): The first carbon-coated lithium iron phosphate and the second carbon-coated lithium iron phosphate are mixed in a mass ratio of (2-3):1.
[0013] In an optional embodiment, the Dv50 of the first carbon-coated lithium iron phosphate is 0.3 μm to 0.6 μm, and the Dv50 of the second carbon-coated lithium iron phosphate is 1.0 μm to 1.4 μm.
[0014] In a second aspect, the present invention provides a lithium iron phosphate positive electrode material prepared by the preparation method described in the first aspect.
[0015] In a third aspect, the present invention provides a lithium battery, comprising the lithium iron phosphate positive electrode material provided in the second aspect.
[0016] The present invention has the following beneficial effects: (1) The present invention prepares spherical iron phosphate particles by combining a crystal form control method and a seed crystal method. The crystal form control method is to add a polymer monomer during the coprecipitation process. The polymer monomer is 3+ The polymerization is initiated by , and the polymerization process is carried out simultaneously with iron phosphate, thereby inhibiting the disordered growth of the iron phosphate crystal surface, and then controlling the growth of iron phosphate into a spherical morphology. The seed method is to obtain small-particle iron phosphate by coprecipitation reaction at a high concentration of raw materials, and then use it as a seed to further coprecipitate at a low concentration of raw materials to obtain large-particle iron phosphate. The two methods are used in combination to prepare iron phosphate particles with a stable spherical morphology. The iron phosphate particles are further calcined with a lithium source to generate spherical lithium iron phosphate. The spherical lithium iron phosphate can reduce its porosity and bridging phenomenon during the stacking process, thereby reducing the impedance on the electron conduction path, reducing the interface resistance, and improving the rate performance of the battery.
[0017] (2) The present invention utilizes rotary kiln vapor deposition combined with different sintering temperatures to prepare spherical carbon-coated lithium iron phosphate with small and large particle sizes, which are mixed by mass to form a graded distribution. The spherical carbon-coated lithium iron phosphate makes the grading effect better, thereby making the finished lithium iron phosphate positive electrode material have a higher compaction density and electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is the X-ray diffraction pattern of the lithium iron phosphate positive electrode material prepared in Example 1; Figure 2 This is a scanning electron microscope image of the ferric phosphate dihydrate prepared in Example 1; Figure 3 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material prepared in Example 1; Figure 4 This is a transmission electron microscope image of the lithium iron phosphate positive electrode material prepared in Example 1; Figure 5 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art.
[0021] In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present invention and are not intended to limit the subject matter described in the claims. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0022] In the description of the embodiments of the present application, the terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order, or primary and secondary relationship of the indicated technical features. The term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone.
[0023] For simplicity, the present invention specifically discloses some numerical ranges, and various numerical ranges can be combined with each other to form corresponding embodiments. The endpoints and any value of the scope disclosed in the present disclosure are not limited to this accurate scope or value, and these scopes or values should be understood as comprising values close to these scopes or values. For numerical range, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between the separate point value, can be combined with each other and obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article.
[0024] Unless otherwise specified, the terms used in the present invention have the commonly understood meanings that are generally understood by those skilled in the art.
[0025] The following is a detailed description of a lithium iron phosphate positive electrode material, a preparation method thereof, and a lithium battery provided by the present invention.
[0026] The present invention provides a method for preparing a lithium iron phosphate positive electrode material, which comprises the following steps: S1. Performing a first coprecipitation reaction on a solution of a first iron source and a solution of a first phosphorus source in the presence of a polymer monomer to obtain iron phosphate seed crystals.
[0027] S2. Performing a second coprecipitation reaction on the solution of the second iron source and the solution of the second phosphorus source in the presence of a polymer monomer and iron phosphate seed crystals to obtain iron phosphate dihydrate.
[0028] In some embodiments, the concentration of the solution of the first iron source and the solution of the first phosphorus source is 1mol / L~2mol / L, for example, it can be any one of 1mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L, 2.0mol / L, or a range value between any two of them; the concentration of the solution of the second iron source and the solution of the second phosphorus source is 0.1mol / L~0.5mol / L, for example, it can be any one of 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, or a range value between any two of them.
[0029] In some embodiments, the amount of iron phosphate seed crystals added is 10% to 25% of the total mass of the second iron source and the second phosphorus source, for example, it can be any one of 10%, 15%, 20%, 25% or a range value between any two of them.
[0030] The particle size of the material is controlled by regulating the concentration of the iron source solution and the phosphorus source solution to prepare iron phosphate seeds with small particle size and iron phosphate dihydrate with large particle size. In the first coprecipitation reaction, a high-concentration first iron source solution and a first phosphorus source solution are used, the raw material solution concentration is high, and the crystal nucleation rate is greater than the crystal growth rate, so mainly small-particle-sized iron phosphate seeds are generated. In the second coprecipitation reaction, a low-concentration second iron source solution and a second phosphorus source solution are used, the raw material solution concentration is low, the seed nucleation rate is less than the crystal growth rate, and it is more inclined to continue to grow on the iron phosphate seeds present in the reaction system, so large-particle-sized iron phosphate dihydrate is generated.
[0031] In some embodiments, the polymer monomer includes at least one of pyrrole, aniline and thiophene; the amount of the polymer monomer per gram of iron source is 0.01g~0.2g, for example, it can be any one of 0.01g, 0.05g, 0.1g, 0.15g, 0.2g or a range between any two of them.
[0032] During the coprecipitation reaction, the polymer monomer is introduced, and the Fe in the iron source solution 3+ As an initiator, the polymer monomer is polymerized in situ. The in situ polymerization and the growth of iron phosphate are carried out simultaneously, so the disordered growth of the iron phosphate crystal surface can be inhibited, and the iron phosphate growth can be controlled to be spherical. Secondly, the long-chain polymer formed by the monomer reaction polymerization can be used as a carbon source, thereby reducing the amount of external carbon source used in the subsequent preparation of lithium iron phosphate.
[0033] During the coprecipitation reaction, the polymer monomer is introduced to adjust the concentration of the raw material solution, so that the iron phosphate seeds with small particle size have a spherical morphology, and then the large particles of iron phosphate dihydrate prepared by the seeds also have a spherical morphology.
[0034] In some embodiments, the first coprecipitation reaction and / or the second coprecipitation reaction includes adding a morphology control agent. The morphology control agent includes at least one of polyethylene glycol, polyvinyl pyrrolidone and hexadecyl trimethyl ammonium bromide. The mass of the morphology control agent is 0.01% to 5% of the mass of the first iron source or the second iron source, for example, it can be any one of 0.01%, 0.1%, 1%, 3%, 5% or any range between the two. The morphology control agent can regulate the primary particle morphology of iron phosphate, thereby obtaining iron phosphate with uniform morphology.
[0035] In some embodiments, the first coprecipitation reaction and / or the second coprecipitation reaction comprises adding an oxidant and / or a pH adjuster, wherein the oxidant comprises hydrogen peroxide and the pH adjuster comprises ammonia. 2+ When an oxidant is added, Fe 2+ Converted to Fe 3+ Participate in co-precipitation reaction.
[0036] In some embodiments, the pH of the first coprecipitation reaction and / or the second coprecipitation reaction is 1.5~3.0, for example, it can be any one of 1.5, 2.0, 2.5, 3.0 or a range value between any two of them; the temperature of the first coprecipitation reaction and / or the second coprecipitation reaction is 75°C~95°C, for example, it can be any one of 75°C, 80°C, 85°C, 90°C, 95°C or a range value between any two of them.
[0037] In some embodiments, after the first coprecipitation reaction and / or the second coprecipitation is completed, aging and solid-liquid separation are further included, and the separated solid product is dried; wherein the aging time is 0.5h~6h, the drying temperature is 100℃~130℃, and the drying time is 2h~5h. The completion of the first coprecipitation reaction and / or the second coprecipitation means that the ion concentration in the coprecipitation reaction system no longer changes.
[0038] In summary, by introducing polymerization monomers and adjusting the concentration of the raw material solution during the coprecipitation reaction, small-sized spherical iron phosphate seeds are first prepared, and then the small-sized spherical iron phosphate seeds are used to promote crystallization to further generate large-sized spherical iron phosphate dihydrate.
[0039] In the coprecipitation reaction system, ammonia water is not only a pH regulator, but also its NH4 + It will be complexed on the surface of iron phosphate. In the subsequent sintering process to prepare lithium iron phosphate, NH4 + It will become NH3 to form pores and make the material porous, which will accelerate the transmission of lithium ions and improve the electrical performance. Unlike other researchers who also roast dihydrate iron phosphate to obtain anhydrous iron phosphate, the present invention does not roast dihydrate iron phosphate because NH4 + Converting into NH3 will destroy the spherical morphology of the iron phosphate material, which is not conducive to the subsequent preparation of spherical lithium iron phosphate.
[0040] S3, mixing ferric phosphate dihydrate, a lithium source and a carbon source, and spray-drying the mixture to obtain a spray material.
[0041] The mixing technique includes sand grinding.
[0042] In some embodiments, the carbon source includes at least one of sucrose, glucose, cyclodextrin, cellulose, tannic acid, polyethylene glycol, vitamin C, and asphalt.
[0043] In some embodiments, the molar ratio of Fe to Li in the spray material is 1:(1-1.05), and the mass of the carbon source accounts for 4%-12% of the total mass of the ferric phosphate dihydrate and the lithium source.
[0044] In some embodiments, the inlet air temperature of the spray drying is 200°C to 230°C, and the outlet air temperature is 90°C to 110°C.
[0045] S4, placing the spray material in a rotary kiln for sintering to obtain carbon-coated lithium iron phosphate; wherein different sintering temperatures are set to respectively prepare the first carbon-coated lithium iron phosphate and the second carbon-coated lithium iron phosphate.
[0046] In some embodiments, the sintering includes sintering for 3 to 8 hours and then introducing a reducing gas for 1 to 5 hours. The reducing gas includes at least one of acetylene and methane, and the gas flow rate is 0.01 L / min to 0.15 L / min, for example, any one of 0.01 L / min, 0.03 L / min, 0.05 L / min, 0.07 L / min, 0.09 L / min, 0.11 L / min, 0.13 L / min, 0.15 L / min, or a range between any two of them.
[0047] The spray material is sintered in a uniformly heated rotary kiln, so that the lithium iron phosphate is evenly heated during the growth process, which facilitates the acquisition of lithium iron phosphate with uniform particle size. At the same time, in the later stage of the sintering process, a reducing gas is introduced for vapor deposition to obtain lithium iron phosphate with a carbon coating layer. Vapor deposition can increase the graphitization degree of the carbon coating layer, thereby improving the conductivity and rate performance of the carbon-coated lithium iron phosphate.
[0048] In some embodiments, the sintering temperature corresponding to the first carbon-coated lithium iron phosphate is 730°C to 770°C, for example, it can be any one of 730°C, 740°C, 750°C, 760°C, 770°C, or a range between any two thereof. The sintering temperature corresponding to the second carbon-coated lithium iron phosphate is 800°C to 830°C, for example, it can be any one of 800°C, 810°C, 820°C, 830°C, or a range between any two thereof.
[0049] The particle size of carbon-coated lithium iron phosphate can be controlled by adjusting the sintering temperature. When the sintering temperature is low, such as 730℃~770℃, the crystal growth is slow, so the particle size of the first carbon-coated lithium iron phosphate is small, 0.3μm~0.6μm; when the sintering temperature is high, such as 800℃~830℃, the crystal growth is fast, so the particle size of the second carbon-coated lithium iron phosphate is large, 1.0μm~1.4μm.
[0050] As a precursor of lithium iron phosphate, the morphology of iron phosphate will directly affect the morphology of lithium iron phosphate, and spherical iron phosphate often leads to spherical lithium iron phosphate. Therefore, when the spherical iron phosphate obtained by S2 is used as a precursor in the present invention, the prepared carbon-coated lithium iron phosphate has a spherical morphology. The spherical morphology of carbon-coated lithium iron phosphate makes the contact area between adjacent particles larger, reduces the porosity and bridging phenomenon during the stacking process, thereby reducing the impedance on the electron conduction path, reducing the interface resistance, and improving the electrical performance of the battery.
[0051] S5. Mix the first carbon-coated lithium iron phosphate and the second carbon-coated lithium iron phosphate in a mass ratio of (2-3):1 to obtain a lithium iron phosphate positive electrode material.
[0052] In some embodiments, the Dv50 of the first carbon-coated lithium iron phosphate is 0.3μm~0.6μm, for example, it can be any one of 0.3μm, 0.4μm, 0.5μm, 0.6μm or a range value between any two of them; the Dv50 of the second carbon-coated lithium iron phosphate is 1.0μm~1.4μm, for example, it can be any one of 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm or a range value between any two of them.
[0053] The first carbon-coated lithium iron phosphate and the second carbon-coated lithium iron phosphate are mixed in a mass ratio to form a graded distribution, and the small-particle size of the first carbon-coated lithium iron phosphate is filled in the gaps between the large-particle size of the second carbon-coated lithium iron phosphate, thereby improving the overall compaction density of the material.
[0054] In summary, the spherical morphology of carbon-coated lithium iron phosphate is prepared and the large and small particles of carbon-coated lithium iron phosphate are used to form a graded distribution. The two work together to make the prepared lithium iron phosphate positive electrode material have a high compaction density and high rate performance.
[0055] The features and performances of the present invention are further described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples.
[0056] Example 1 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method thereof includes: S1. Add 1.0 mol / L ferrous sulfate solution and 1.0 mol / L phosphoric acid solution to the reactor, stir evenly, add polyethylene glycol, hydrogen peroxide and pyrrole, add ammonia water to adjust the pH of the system in the reactor to 2.0, and perform the first coprecipitation reaction at 90° C. After the first coprecipitation reaction is completed, age for 1 hour, separate the solid and liquid, and dry the separated solid product at 110° C. for 4 hours to obtain iron phosphate seed crystals.
[0057] The molar ratio of ferrous sulfate: phosphoric acid: hydrogen peroxide is 1:1:1, the mass of polyethylene glycol is 1% of the mass of ferrous sulfate, and the amount of pyrrole corresponding to each gram of ferrous sulfate is 0.05 g.
[0058] S2, add 0.5mol / L ferrous sulfate solution and 0.5mol / L phosphoric acid solution to the reactor, stir evenly, add iron phosphate seed, polyethylene glycol, hydrogen peroxide and pyrrole, add ammonia water to adjust the pH of the system in the reactor to 2.0, and carry out the second coprecipitation reaction at 95° C. After the second coprecipitation reaction is completed, age for 4h, separate the solid and liquid, and dry the separated solid product at 130° C. for 5h to obtain dihydrated iron phosphate.
[0059] Among them, the molar ratio of ferrous sulfate: phosphoric acid: hydrogen peroxide is 1:1:1; the mass of polyethylene glycol is 0.05% of the mass of ferrous sulfate; the amount of pyrrole corresponding to each gram of ferrous sulfate is 0.05g; the amount of iron phosphate seed added is 20% of the total mass of ferrous sulfate and phosphoric acid in S2.
[0060] S3, grinding ferrous phosphate dihydrate, lithium carbonate and glucose to mix evenly, and then spray drying to obtain a spray material.
[0061] Among them, the molar ratio of ferric phosphate dihydrate and lithium carbonate is 1:1.04; the mass of glucose accounts for 8% of the total mass of ferric phosphate dihydrate and lithium carbonate; the inlet temperature of spray drying is 220°C, and the outlet temperature is 95°C.
[0062] S4. After the spray material is placed in a rotary kiln for sintering for 5 hours under a nitrogen atmosphere, acetylene gas is introduced and sintering is continued for 3 hours to obtain carbon-coated lithium iron phosphate. The sintering temperatures are set to 750° C. to prepare the first carbon-coated lithium iron phosphate and 820° C. to prepare the second carbon-coated lithium iron phosphate.
[0063] Among them, the gas flow rate is 0.06L / min.
[0064] S5. Mix the first carbon-coated lithium iron phosphate and the second carbon-coated lithium iron phosphate in a mass ratio of 2.3:1 to obtain a lithium iron phosphate positive electrode material.
[0065] Attached Figure 1 This is the X-ray diffraction diagram of the lithium iron phosphate positive electrode material obtained in this example. It can be seen that its peak position and intensity correspond one-to-one with the standard card, proving that the prepared substance is lithium iron phosphate.
[0066] Attached Figure 2 This is a scanning electron microscope image of the ferric phosphate dihydrate obtained in this example. It can be seen that the morphology of the ferric phosphate is spherical particles formed by the agglomeration of primary particles.
[0067] Attached Figure 3 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material obtained in this example. It can be seen that the lithium iron phosphate positive electrode material has a spherical morphology, and its particles are large and small, with small particles being the majority.
[0068] Attached Figure 4 This is a transmission electron microscope image of the lithium iron phosphate positive electrode material obtained in this embodiment. It can be seen that the carbon layer is evenly coated on the surface of the lithium iron phosphate with a thickness of about 1nm~2nm. This uniform carbon layer is beneficial to improving the conductivity of the material, thereby improving the rate performance of the material. Example 2 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method thereof includes: S1. Add 1.5 mol / L ferrous sulfate solution and 1.5 mol / L phosphoric acid solution to the reactor, stir evenly, add polyethylene glycol, hydrogen peroxide and thiophene, add ammonia water to adjust the pH of the system in the reactor to 1.5, and perform the first coprecipitation reaction at 75° C. After the first coprecipitation reaction is completed, age for 6 hours, separate the solid and liquid, and dry the separated solid product at 100° C. for 2 hours to obtain iron phosphate seed crystals.
[0069] The molar ratio of ferrous sulfate: phosphoric acid: hydrogen peroxide is 1:1:1, the mass of polyethylene glycol is 5% of the mass of ferrous sulfate, and the amount of thiophene corresponding to each gram of ferrous sulfate is 0.01 g.
[0070] S2. Add 0.1 mol / L ferrous sulfate solution and 0.1 mol / L phosphoric acid solution to the reactor, stir evenly, add iron phosphate seeds, polyethylene glycol, hydrogen peroxide and thiophene, add ammonia water to adjust the pH of the system in the reactor to 1.5, and perform a second coprecipitation reaction at 90° C. After the second coprecipitation reaction is completed, age for 4 hours, separate the solid and liquid, and dry the separated solid product at 130° C. for 5 hours to obtain dihydrated iron phosphate.
[0071] Among them, the molar ratio of ferrous sulfate: phosphoric acid: hydrogen peroxide is 1:1:1; the mass of polyethylene glycol is 0.01% of the mass of ferrous sulfate; the amount of thiophene corresponding to each gram of ferrous sulfate is 0.1g; the amount of iron phosphate seed added is 10% of the total mass of ferrous sulfate and phosphoric acid in S2.
[0072] S3, grinding and mixing ferrous phosphate dihydrate, lithium carbonate and tannic acid uniformly, and then spray drying to obtain a spray material.
[0073] Among them, the molar ratio of iron phosphate dihydrate and lithium carbonate is 1:1; the mass of tannic acid accounts for 12% of the total mass of iron phosphate dihydrate and lithium carbonate; the inlet air temperature of spray drying is 220°C, and the outlet air temperature is 90°C.
[0074] S4. After the spray material is placed in a rotary kiln for sintering for 3 hours under a nitrogen atmosphere, acetylene gas is introduced and sintering is continued for 5 hours to obtain carbon-coated lithium iron phosphate. The sintering temperatures are set to 730° C. to prepare the first carbon-coated lithium iron phosphate and 830° C. to prepare the second carbon-coated lithium iron phosphate.
[0075] Among them, the gas flow rate is 0.01L / min.
[0076] S5. Mix the first carbon-coated lithium iron phosphate and the second carbon-coated lithium iron phosphate in a mass ratio of 2:1 to obtain a lithium iron phosphate positive electrode material.
[0077] Example 3 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method thereof includes: S1. Add 2.0 mol / L ferrous sulfate solution and 2.0 mol / L phosphoric acid solution to the reactor, stir evenly, add polyethylene glycol, hydrogen peroxide and pyrrole, add ammonia water to adjust the pH of the system in the reactor to 3.0, and perform the first coprecipitation reaction at 80° C. After the first coprecipitation reaction is completed, age for 1 h, separate the solid and liquid, and dry the separated solid product at 130° C. for 5 h to obtain iron phosphate seed crystals.
[0078] The molar ratio of ferrous sulfate: phosphoric acid: hydrogen peroxide is 1:1.01:1.1, the mass of polyethylene glycol is 2% of the mass of ferrous sulfate, and the amount of pyrrole corresponding to each gram of ferrous sulfate is 0.01 g.
[0079] S2. Add 0.3 mol / L ferrous sulfate solution and 0.3 mol / L phosphoric acid solution to the reactor, stir evenly, add iron phosphate seed, hexadecyltrimethylammonium bromide, hydrogen peroxide and pyrrole, add ammonia water to adjust the pH of the system in the reactor to 2.0, and perform a second coprecipitation reaction at 95° C. After the second coprecipitation reaction is completed, age for 3 hours, separate the solid and liquid, and dry the separated solid product at 100° C. for 5 hours to obtain dihydrated iron phosphate.
[0080] Among them, the molar ratio of ferrous sulfate: phosphoric acid: hydrogen peroxide is 1:1:1.1; the mass of hexadecyltrimethylammonium bromide is 3% of the mass of ferrous sulfate; the amount of pyrrole corresponding to each gram of ferrous sulfate is 0.2g; the amount of iron phosphate seed added is 25% of the total mass of ferrous sulfate and phosphoric acid in S2.
[0081] S3, grinding ferrous phosphate dihydrate, lithium carbonate and glucose to mix evenly, and then spray drying to obtain a spray material.
[0082] Among them, the molar ratio of ferric phosphate dihydrate and lithium carbonate is 1:1.05; the mass of glucose accounts for 4% of the total mass of ferric phosphate dihydrate and lithium carbonate; the inlet temperature of spray drying is 220°C, and the outlet temperature is 108°C.
[0083] S4. After the spray material is placed in a rotary kiln for sintering for 8 hours under a nitrogen atmosphere, methane gas is introduced and sintered for 1 hour to obtain carbon-coated lithium iron phosphate. The sintering temperatures are set to 770° C. to prepare the first carbon-coated lithium iron phosphate and 800° C. to prepare the second carbon-coated lithium iron phosphate.
[0084] Among them, the gas flow rate is 0.15L / min.
[0085] S5. Mix the first carbon-coated lithium iron phosphate and the second carbon-coated lithium iron phosphate in a mass ratio of 3:1 to obtain a lithium iron phosphate positive electrode material.
[0086] Example 4 This embodiment provides a lithium iron phosphate positive electrode material, which is different from the embodiment 1 only in that the amount of pyrrole used per gram of ferrous sulfate in S1 is 0.02 g.
[0087] Example 5 This embodiment provides a lithium iron phosphate positive electrode material, which is different from the embodiment 1 only in that the amount of pyrrole used per gram of ferrous sulfate in S1 is 0.15 g.
[0088] Example 6 This embodiment provides a lithium iron phosphate positive electrode material, which is different from the embodiment 1 only in that the amount of pyrrole used per gram of ferrous sulfate in S2 is 0.02 g.
[0089] Example 7 This embodiment provides a lithium iron phosphate positive electrode material, which is different from the embodiment 1 only in that the amount of pyrrole used per gram of ferrous sulfate in S2 is 0.1 g.
[0090] Example 8 This embodiment provides a lithium iron phosphate positive electrode material, which is different from the embodiment 1 only in that the amount of pyrrole used per gram of ferrous sulfate in S2 is 0.18 g.
[0091] Example 9 This embodiment provides a lithium iron phosphate positive electrode material, which is different from the embodiment 1 only in that in S2, the amount of iron phosphate seed crystals added is 15%.
[0092] Example 10 This embodiment provides a lithium iron phosphate positive electrode material, which is different from the embodiment 1 only in that in S2, the amount of iron phosphate seed crystals added is 23%.
[0093] Embodiment 11 This embodiment provides a lithium iron phosphate positive electrode material, which is different from Embodiment 1 only in that polyethylene glycol is not added in S2.
[0094] Comparative Example 1 This comparative example provides a lithium iron phosphate positive electrode material, which is different from Example 1 only in that pyrrole is not added to S1.
[0095] Attached Figure 5 The scanning electron microscope image of the lithium iron phosphate positive electrode material obtained in this comparative example shows that the lithium iron phosphate positive electrode material has a spherical morphology, with particles of different sizes, and the larger the particles, the more obvious their edges and corners.
[0096] Comparative Example 2 This comparative example provides a lithium iron phosphate positive electrode material, which differs from Example 1 in that pyrrole is not added to S1 and S2.
[0097] Comparative Example 3 This comparative example provides a lithium iron phosphate positive electrode material, which differs from Example 1 in that S1 is absent, that is, no iron phosphate seed crystals are added to S2.
[0098] Comparative Example 4 This comparative example provides a lithium iron phosphate positive electrode material, which differs from Example 1 in that acetylene gas is not introduced during the rotary kiln sintering process of S4.
[0099] Comparative Example 5 This comparative example provides a lithium iron phosphate positive electrode material, which differs from Example 1 in that a roller kiln is used for sintering during the sintering process of S4, and acetylene gas is not introduced.
[0100] Comparative Example 6 This comparative example provides a lithium iron phosphate positive electrode material, which is different from Example 1 in that the lithium iron phosphate positive electrode material in S5 is only the first carbon-coated lithium iron phosphate.
[0101] Comparative Example 7 This comparative example provides a lithium iron phosphate positive electrode material, which is different from Example 1 in that the lithium iron phosphate positive electrode material in S5 is only the second carbon-coated lithium iron phosphate.
[0102] Test Example 1 The crystal structure of lithium iron phosphate positive electrode material was tested using an X-ray diffractometer.
[0103] Test Example 2 Scanning electron microscopy and transmission electron microscopy were used to test the microstructure of lithium iron phosphate positive electrode materials.
[0104] Test Example 3 The size and distribution of the lithium iron phosphate positive electrode material particles were tested using a laser particle size analyzer. The particle size test results were expressed as Dv50. The test results are shown in Table 1.
[0105] Test Example 4 The lithium iron phosphate positive electrode material was tested using a Sansi vertical and horizontal compaction density instrument, and the test results are shown in Table 1.
[0106] Test Example 5 The lithium iron phosphate positive electrode material, acetylene black and polyvinylidene fluoride obtained in the above examples and comparative examples are uniformly mixed in N-methylpyrrolidone at a mass ratio of 90:5:5, then coated on aluminum foil and placed in a vacuum drying oven for drying. After drying, a tablet press is used to press the positive electrode sheet. According to: negative electrode shell-lithium sheet-LiPF6 electrolyte-celgard2500 diaphragm-LiPF6 electrolyte-positive electrode sheet-gasket-spring-positive electrode shell, assemble into a button battery and let it stand in a constant temperature box at 25°C for 10 hours. After standing, the button battery is tested for electrochemical performance using the LAND battery testing system, and the voltage range is: 2.0V~3.75V. The test results are shown in Table 1.
[0107] Table 1
[0108] As can be seen from Table 1, from Examples 1, 4 to 8 and Comparative Examples 1 to 2, the presence and amount of pyrrole will affect the morphology of iron phosphate, and then affect the morphology and physicochemical properties of lithium iron phosphate. Iron phosphate dihydrate was prepared without adding pyrrole, and the morphology of lithium iron phosphate synthesized therefrom was non-spherical. This shows that the presence of polymer monomers can control the growth of iron phosphate crystal surfaces to synthesize spherical iron phosphate, and then synthesize spherical lithium iron phosphate. When the amount of pyrrole is too low, the coated carbon content will be low, and the electronic conductivity and the capacity at 5C rate will be limited. When the amount of pyrrole is too high, the coated carbon layer is thicker, which affects the compaction performance of the material.
[0109] It can be seen from Examples 1, 9-10 and Comparative Example 3 that when preparing ferric phosphate dihydrate, no seed crystals are added. In the synthesis process of low-concentration raw materials, the seed crystal nucleation rate is slow, which makes the particles larger and the morphology is easy to change, resulting in poor spherical morphology, which in turn leads to poor spherical morphology of subsequent lithium iron phosphate positive electrode materials, and low compaction density and electrochemical performance. The amount of seed crystal added will affect the particle size of the material. When the amount added is small, the added seed crystals are not enough to consume the supersaturation in the mother liquor, and the growth sites provided by the seed crystals are small, resulting in too many uncontrollable factors in the crystal growth process, making the particle size distribution uneven; when the amount added is too much, the material particle size will be small, and the contact area with the electrolyte will increase, affecting the electrical properties of the lithium iron phosphate positive electrode material.
[0110] It can be seen from Example 1 and Comparative Examples 4-5 that the rate performance of the lithium iron phosphate positive electrode material without a high graphitized carbon coating layer formed by vapor deposition is low.
[0111] It can be seen from Example 1 and Comparative Examples 6-7 that grading can improve the compaction density and electrochemical performance of lithium iron phosphate positive electrode materials. When there are only large particles or only small particles in the lithium iron phosphate positive electrode material, its compaction density is limited. Only by filling the small particles into the gaps between the large particles in a certain proportion can the compaction improvement space be maximized.
[0112] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The steps include: S1, subjecting a first iron source solution and a first phosphorus source solution to a first coprecipitation reaction in the presence of a polymer monomer to obtain iron phosphate seed crystals; S2, subjecting the second iron source solution and the second phosphorus source solution to a second coprecipitation reaction in the presence of the polymer monomer and the iron phosphate seed crystals to obtain iron phosphate dihydrate; S3, mixing the ferric phosphate dihydrate, the lithium source and the carbon source and spray drying the mixture to obtain a spray material; S4, placing the spray material in a rotary kiln for sintering to obtain carbon-coated lithium iron phosphate; wherein different sintering temperatures are set to respectively prepare a first carbon-coated lithium iron phosphate and a second carbon-coated lithium iron phosphate; S5. Mix the first carbon-coated lithium iron phosphate and the second carbon-coated lithium iron phosphate according to a mass ratio to obtain a lithium iron phosphate positive electrode material.
2. The preparation method according to claim 1, characterized in that: The concentrations of the first iron source solution and the first phosphorus source solution are 1 mol / L to 2 mol / L, and the concentrations of the second iron source solution and the second phosphorus source solution are 0.1 mol / L to 0.5 mol / L.
3. The preparation method according to claim 1, characterized in that: The amount of the iron phosphate seed crystals added is 10% to 25% of the total mass of the second iron source and the second phosphorus source.
4. The preparation method according to claim 1, characterized in that: The polymer monomer satisfies at least one of the following (1) to (2): (1): The polymer monomer includes at least one of pyrrole, aniline and thiophene; (2): In steps S1 and S2, the amount of the polymer monomer used per gram of iron source is 0.01 g to 0.2 g.
5. The preparation method according to claim 1, characterized in that: The first coprecipitation reaction and / or the second coprecipitation reaction satisfies at least one of the following (3) to (6): (3): The coprecipitation reaction includes adding a morphology control agent, wherein the morphology control agent includes at least one of polyethylene glycol, polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide, and the mass of the morphology control agent is 0.01% to 5% of the mass of the first iron source or the second iron source; (4): The coprecipitation reaction includes adding an oxidant and / or a pH adjuster, wherein the oxidant includes hydrogen peroxide and the pH adjuster includes ammonia water; (5): The pH of the coprecipitation reaction is 1.5~3.0, and the temperature of the coprecipitation reaction is 75℃~95℃; (6): After the coprecipitation reaction is completed, it also includes aging and solid-liquid separation, and drying the separated solid product; wherein the aging time is 0.5h~6h, the drying temperature is 100℃~130℃, and the drying time is 2h~5h.
6. The preparation method according to claim 1, characterized in that: The sintering in step S4 includes sintering for 3h~8h and then introducing reducing gas to continue sintering for 1h~5h; The reducing gas includes at least one of acetylene and methane, and the gas flow rate is 0.01L / min~0.15L / min.
7. The preparation method according to claim 1, characterized in that: Satisfy at least one of the following (7) to (9): (7): The sintering temperature of the first carbon-coated lithium iron phosphate is 730°C to 770°C; (8): The sintering temperature of the second carbon-coated lithium iron phosphate is 800°C to 830°C; (9): The first carbon-coated lithium iron phosphate and the second carbon-coated lithium iron phosphate are mixed in a mass ratio of (2-3):
1.
8. The preparation method according to claim 1, characterized in that: The Dv50 of the first carbon-coated lithium iron phosphate is 0.3 μm to 0.6 μm, and the Dv50 of the second carbon-coated lithium iron phosphate is 1.0 μm to 1.4 μm.
9. A lithium iron phosphate positive electrode material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.
10. A lithium battery, characterized in that: Including the lithium iron phosphate positive electrode material as described in claim 9.
Citation Information
Patent Citations
High-compaction low-temperature lithium iron phosphate material, lithium battery positive plate and preparation method thereof
CN113086959A
Lithium manganese iron phosphate precursor as well as preparation method and application thereof
CN115849324A
Secondary growth preparation method of nano lithium iron phosphate
CN116409772A
Nanometer iron phosphate and preparation method thereof, nanometer lithium iron phosphate positive electrode material and preparation method and application of nanometer lithium iron phosphate positive electrode material
CN117602603A
Lithium manganese-iron phosphate particles, lithium manganese-iron phosphate powders and their preparation methods
TWI625888B
Cited By
Lithium iron phosphate positive electrode material, preparation method thereof and lithium battery
CN119890280A
Preparation method of high-productivity sodium ion battery positive electrode material
CN121591266A
Iron phosphate with gradient particle size, lithium iron phosphate with gradient particle size, preparation method of iron phosphate and lithium ion battery
CN122355254A
Iron phosphate, lithium iron phosphate of gradient particle size, preparation method thereof and lithium ion battery
CN122355254B